Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.11628/ksppe.2021.24.6.585
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chemical Compounds of Gaseous and Particulate Pollutants from the Open Burning of Agricultural HDPE Film Waste

Abstract: Background and objective: Illegal open-air incineration, which is criticized as a leading source of air pollutants among agricultural activities, currently requires constant effort and attention. Countries around the world have been undertaking studies on the emission of heavy metal substances in fine dust discharged during the incineration process. A precise analytical method is required to examine the harmful effects of particulate pollutants on the human body.Methods: In order to simulate open-air incinerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…5). As in the previous study (Kim et al, 2021), an SEM-EDS analysis of those chemical species found that the weight ratio of transition and other metals was relatively low in the fine particles with equal content of non-metals C and O compared to those with a low content of non-metal C. This was considered to be similar to the irregular shapes of rock-shaped particles found in this study. Compared to the rock-shaped particles, cotton-shaped particles with various sizes ranging from 5 μm to 20 μm were observed in the form of fluffy bundles, and were mainly small, in a size of 10 μm.…”
Section: Sem-eds Analysis Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…5). As in the previous study (Kim et al, 2021), an SEM-EDS analysis of those chemical species found that the weight ratio of transition and other metals was relatively low in the fine particles with equal content of non-metals C and O compared to those with a low content of non-metal C. This was considered to be similar to the irregular shapes of rock-shaped particles found in this study. Compared to the rock-shaped particles, cotton-shaped particles with various sizes ranging from 5 μm to 20 μm were observed in the form of fluffy bundles, and were mainly small, in a size of 10 μm.…”
Section: Sem-eds Analysis Resultssupporting
confidence: 89%
“…Since the element was reported to be emitted into the atmosphere during combustion of coal, fossil fuels and waste (Koukoulakis et al, 2019), it seemed to be detected at a higher frequency after burning. Previous studies using the same experimental infrastructure reported that chemical species corresponding to transition metals and metalloids were detected from the open burning of agricultural HDPE film waste through an SEM-EDS analysis (Kim et al, 2021).…”
Section: Xrf Analysis Resultsmentioning
confidence: 95%